Evaluation of the Level of Statistical Association between the Gross Domestic Product and the Percentage of Male Population among Colombian Emigrants - William Niebles -Núñez; Alexander Perez Cordero; Donicer E Montes Vergara (Migration Letters, 2023)
In the context of Colombia’s changing migration landscape, this study delves into the specific cohort of Colombian male emigrants, with the aim of unraveling the intricate relationship between economic dynamics and male emigration patterns. In this context, the variation in Colombia’s Gross Domestic Product (GDP) emerges as a fundamental economic indicator, which reflects the economic vitality, growth prospects and employment possibilities of the nation. In turn, male Colombian emigrants represent a notable facet of the broader emigration phenomenon, and their journeys are influenced by a variety of motivations, including economic opportunities, educational pursuits, and personal aspirations. In this way, for the purposes of this study, two variables have been parameterized to measure the level of association between them through a correlational study, these being the “Percentage variation of the Gross Domestic Product (GDP)” and the “Percentage variation of emigrants Colombian men". Subsequently, the data collected have been evaluated with exhaustive statistical evaluation analysis using Pearson’s evaluation coefficient, which has resulted in a remarkably low P-Value of 0.0001221, much lower than the significance level 𝛂 = 0.05, which has allowed us to conclude that the relationship between both variables is significant, and likewise, a Pearson correlation coefficient of 0.92, which shows a strong positive correlation between the variables studied. These results reveal a statistically significant association between the fluctuations of the GDP and Colombian male emigration, with sufficient statistical evidence to affirm that, as Colombia’s GDP grows or decreases, there is a synchronous increase or decrease in the number of Colombian male emigrants.